Safety and efficacy of MVA85A, a new tuberculosis vaccine, in infants previously vaccinated with BCG: a randomised, placebo-controlled phase 2b trial. - Tameris, MD; Hatherill, M; Landry, B; Scriba, T; Snowden, M; Lockhart, S; Shea, J; McClain, J; Hussey, G; Hanekom, W; Mahomed, H; McShane, H (2013)
BACKGROUND: BCG vaccination provides incomplete protection against tuberculosis in infants. A new vaccine, modified Vaccinia Ankara virus expressing antigen 85A (MVA85A), was designed to enhance the protective efficacy of BCG. We aimed to assess safety, immunogenicity, and efficacy of MVA85A against tuberculosis and Mycobacterium tuberculosis infection in infants. METHODS: In our double-blind, randomised, placebo-controlled phase 2b trial, we enrolled healthy infants (aged 4–6 months) without HIV infection who had previously received BCG vaccination. We randomly allocated infants (1:1), according to an independently generated sequence with block sizes of four, to receive one intradermal dose of MVA85A or an equal volume of Candida skin test antigen as placebo at a clinical facility in a rural region near Cape Town, South Africa. We actively followed up infants every 3 months for up to 37 months. The primary study outcome was safety (incidence of adverse and serious adverse events) in all vaccinated participants, but we also assessed efficacy in a protocol-defined group of participants who received at least one dose of allocated vaccine. The primary efficacy endpoint was incident tuberculosis incorporating microbiological, radiological, and clinical criteria, and the secondary efficacy endpoint was M tuberculosis infection according to QuantiFERON TB Gold In-tube conversion (Cellestis, Australia). This trial was registered with the South African National Clinical Trials Register (DOH-27-0109-2654) and with ClinicalTrials.gov on July 31, 2009, number NCT00953927. FINDINGS: Between July 15, 2009, and May 4, 2011, we enrolled 2797 infants (1399 allocated MVA85A and 1398 allocated placebo). Median follow-up in the per-protocol population was 24·6 months (IQR 19·2–28·1), and did not differ between groups. More infants who received MVA85A than controls had at least one local adverse event (1251 [89%] of 1399 MVA85A recipients and 628 [45%] of 1396 controls who received the allocated intervention) but the numbers of infants with systemic adverse events (1120 [80%] and 1059 [76%]) or serious adverse events (257 [18%] and 258 (18%) did not differ between groups. None of the 648 serious adverse events in these 515 infants was related to MVA85A. 32 (2%) of 1399 MVA85A recipients met the primary efficacy endpoint (tuberculosis incidence of 1·15 per 100 person-years [95% CI 0·79 to 1·62]; with conversion in 178 [13%] of 1398 infants [95% CI 11·0 to 14·6]) as did 39 (3%) of 1395 controls (1·39 per 100 person-years [1·00 to 1·91]; with conversion in 171 [12%] of 1394 infants [10·6 to 14·1]). Efficacy against tuberculosis was 17·3% (95% CI −31·9 to 48·2) and against M tuberculosis infection was −3·8% (–28·1 to 15·9). INTERPRETATION: MVA85A was well tolerated and induced modest cell-mediated immune responses. Reasons for the absence of MVA85A efficacy against tuberculosis or M tuberculosis infection in infants need exploration. FUNDING: Aeras, Wellcome Trust, and Oxford-Emergent Tuberculosis Consortium (OETC).